Pengaruh Idiosinkratik Justin Trudeau dalam Kebijakan Luar Negeri Kanada : Studi Kasus Penerimaan Pengungsi Suriah - Sonia Tiosstar Batubara; Mohammad Rosyidin; Marten Hanura (Intermestic: Journal of International Studies, 2021)
Along with the growing political fear of refugees in Western countries, on the other hand Canada resettled more refugees in 2018. Canada has been known as a country with humanist and solidarity identity. But most Canadians disagree with accepting refugees. Canada's refugee policy is often characterized by the face of Justin Trudeau as a leader, indicating the prime minister's personality plays an important role in determining Canadian policy. This study raises the issue that personality of Justin Trudeau is the reason Canada accepts refugees from Syria. This study uses an idiosyncratic approach that analyzes Trudeau's leadership style based on the leader's personality type according to Margaret Hermann. By using content analysis method, this research finds Trudeau has character; high belief to control events, low conceptual complexity, and low distrust of others. This study will show how Trudeau's character shapes the process and outcome of Canada's foreign policy towards Syrian refugees.